La tutoría académica en la enseñanza universitaria: El caso de la Udelar - Ana Maria Fernández Caraballo (Universidade Estadual de Campinas, 2012)
This article deals with the figure of tutorial as it is classically used in university contexts, which is different from other tutorials of a pedagogical nature. The study is about the academic tutorial as a result of the production of knowledge as an exclusive effect of cognizance and the ties between the tutor and the student. A diachronic study was carried out in order to search for the antecedents of this figure. A synchronic study was also carried out, based on documents and interviews to participants in tutorials at the Universidad de la República (UdelaR).